Partial trisomy 8 (trisomy 8q2106 leads to 8qter). - Abuelo, D (1977)
A case of trisomy for part of the long arm of chromosome 8, confirmed by G-banding analysis, in a white male infant is described. The mother carried a reciprocal translocation between chromosome 8 and chromosome 13 (46,XX,t(8;13),(q21:q34). The patient had inherited the translocated chromosome 13 and was thus trisomic for the distal half of the long arm of chromosome 8. He had many of the clinical features of the full trisomy 8 syndrome. As compared with previously reported cases with trisomy of the distal end of chromosome 8, he was more dysmorphic and showed greater developmental retardation.